2011
DOI: 10.1007/s00792-011-0409-9
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal and antitumoral activities of endophytic fungi associated with the Antarctic angiosperms Deschampsia antarctica Desv. and Colobanthus quitensis (Kunth) Bartl.

Abstract: A total of 564 isolates of endophytic fungi were recovered from the plants Deschampsia antarctica and Colobanthus quitensis collected from Antarctica. The isolates were screened against parasites Leishmania amazonensis and Trypanosoma cruzi and against the human tumour cell lines. Of the 313 fungal isolates obtained from D. antarctica and 251 from C. quitensis, 25 displayed biological activity. Nineteen extracts displayed leishmanicidal activity, and six inhibited the growth of at least one tumour cell line. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 30 publications
1
38
0
4
Order By: Relevance
“…The plates were incubated at 10±2 1C for 15 days, and the cultured materials from each Petri dish were then cut and transferred to 50-ml vials containing 35 ml of ethanol. After 48 h at room temperature, the organic phase was decanted, and the solvent was removed under a vacuum centrifuge at 35 1C (Santiago et al, 2012). An aliquot of each dried extract was dissolved in DMSO (Merck) to prepare a 100-mg ml À 1 stock solution, which was stored at À 20 1C.…”
Section: Fungal Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The plates were incubated at 10±2 1C for 15 days, and the cultured materials from each Petri dish were then cut and transferred to 50-ml vials containing 35 ml of ethanol. After 48 h at room temperature, the organic phase was decanted, and the solvent was removed under a vacuum centrifuge at 35 1C (Santiago et al, 2012). An aliquot of each dried extract was dissolved in DMSO (Merck) to prepare a 100-mg ml À 1 stock solution, which was stored at À 20 1C.…”
Section: Fungal Identificationmentioning
confidence: 99%
“…However, the potential of extremophile fungi to produce bioactive compounds is poorly understood. According to Santiago et al (2012), the ability of Antarctic fungi to survive in extreme conditions suggests that they may display unusual biochemical pathways that allow them to generate specific or new molecules that could be used to develop new drugs. Our bioprospecting results show that the extracts from Penicillium sp.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Five millimeter diameter plugs of each endophytic fungus were place at the center of Petri dishes (90 mm diameter), each containing 20 mL of PDA, and cultured for 13 days at 25˚C ± 2˚C [17]. The material from the resulting fungal cultures were cut from the each Petri dish Conidia concentrations were determined photometrically [18] from a standard curve based on absorbance at 625 nm, and suspensions were adjusted with sterile distilled water to a concentration of 1.0 × 10 6 conidia/mL.…”
Section: Cultivation and Extraction Of Fungal Culturesmentioning
confidence: 99%
“…Several studies have demonstrated that endophytic fungi can produce numerous compounds with biological activities of interest, such as antitumor (Jin-long et al, 2011;Chandra, 2012), antimicrobial (Siqueira et al, 2011;Tayung et al, 2012;Bagchi and Banerjee, 2013;Pinheiro et al, 2013;Orlandelli et al, 2015), enzymes (Chandra, 2012), plant growth hormones (Hwang et al, 2011), leishmanicidal (Santiago et al, 2012), cytotoxic compounds and compounds with industrial and pharmaceutical potential (Meng et al, 2011;Wang and Dai, 2011), reinforcing the broad biotechnological potential of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%